Rational construction of a stable Zn4O-based MOF for highly efficient CO2 capture and conversion. Issue 5 (7th December 2017) - Zhou, Hui-Fang; Liu, Bo; Hou, Lei; Zhang, Wen-Yan; Wang, Yao-Yu
Abstract : An exceptionally stable Zn4 O-MOF has been rationally synthesized, which exhibits high CO2 capture and efficient catalytic conversion for CO2 cycloaddition with epoxides under mild conditions. Abstract : By employing a carboxylate ligand derived from benzene-1, 4-dicarboxylate, a chemically stable Zn4 O-based self-penetrating metal–organic framework has been rationally synthesized, which exhibits high CO2 adsorption and efficient catalytic conversion for CO2 cycloaddition.